Metabolic Labeling of Fucosylated Glycans in Developing Zebrafish - Karen W. Dehnert; Brendan J. Beahm; Thinh T. Huynh; Jeremy M. Baskin; Scott T. Laughlin; Wei Wang; Peng Wu; Sharon L. Amacher; Carolyn R. Bertozzi (2011)
Many developmental processes depend on proper fucosylation, but this post-translational modification is difficult to monitor in vivo. Here we applied a chemical reporter strategy to visualize fucosylated glycans in developing zebrafish. Using azide-derivatized analogues of fucose, we metabolically labeled cell-surface glycans and then detected the incorporated azides via copper-free click chemistry with a difluorinated cyclooctyne probe. We found that the fucose salvage pathway enzymes are expressed during zebrafish embryogenesis but that they process the azide-modified substrates inefficiently. We were able to bypass the salvage pathway by using an azide-functionalized analogue of GDP-fucose. This nucleotide sugar was readily accepted by fucosyltransferases and provided robust cell-surface labeling of fucosylated glycans, as determined by flow cytometry and confocal microscopy analysis. We used this technique to image fucosylated glycans in the enveloping layer of zebrafish embryos during the first 5 days of development. This work provides a method to study the biosynthesis of fucosylated glycans in vivo.